Electric Power generation crisis in Nigeria: A Review of causes and solutions - Emovon, Ikuobase; Samuel, Olusegun David; Mgbemena, Chinedum Ogonna; Adeyeri, Michael Kanisuru (International Journal of Integrated Engineering, 2018)
The low power generation in Nigeria had hindered her economic growth and industrialisation. The nation had carried out various reform to ameliorate the electric power crisis but all to no avail. The electric power crisis has made so many industries to relocate to more environmental friendly nations. Furthermore, the terrible state of the nation’s basic infrastructure such as water supply, health care system and petroleum product distribution are all symptom of an economy that is insalubrious because of the nations’ incapability to meet electric power demand. The subject of power generation in Nigeria is interesting, vital and worthy of investigation. Some researchers have investigated the root causes of low power generation in Nigeria and they came up with diverse factors responsible for the lingering electric power crisis. In this research, a review of previous papers in the literature on factors responsible for the low power generation in Nigeria is performed. From the survey, an all-inclusive factors affecting power generation in Nigeria are presented and discussed. On the basis of the number of authors that cited the individual factor, the whole factors are ranked and categorised. Finally, in this paper, general solutions are proffered to minimise /eliminate the major challenges confronting power generation in Nigeria. The research findings revealed that the major challenges confronting power generation in Nigeria are factors such as poor plant maintenance, aged/obsolete equipment and gas pipe line vandalism and that these challenges can be minimised/eliminated through structured maintenance methodology and adequate funding among others.